Analysis of Gas Station Queue System; Case Study Gas Station 13.201.101 on Jalan Jamin Ginting, Medan Baru District, Medan City - Purba, Johana; Simarmata, Roberta; Marbinoto, Mayono Suko (Journal Governance Bureaucratic Review, 2025)
Public Fuel Filling Stations (SPBU) are essential facilities that support transportation by ensuring the availability of fuel for motorized vehicles. However, long queues, particularly during peak hours, often cause traffic congestion, wasted time, and reduced customer satisfaction. These inefficiencies are generally linked to limited service capacity and uneven workload distribution among fuel pumps. This study aims to analyze the queuing system at Gas Station 13.201.101, Jalan Jamin Ginting, Medan, using the M/M/s queuing model and simulation with Arena software. Data were collected through direct observation of vehicle arrivals and service times for motorcycles and cars. Statistical tests, including chi-square and Kolmogorov-Smirnov, were applied to determine the best fit for inter-arrival and service time distributions, which followed exponential and beta distributions, respectively. The results indicate that motorcycles had an average inter-arrival time of 3.8 minutes and a service time of 3.3 minutes, while cars averaged 5.5 minutes between arrivals with 5.9 minutes of service. The theoretical M/M/s analysis showed relatively efficient performance, with less than one minute of waiting time and pump utilization ranging between 32% and 70%. In contrast, Arena simulation reflected real operational conditions more accurately, showing no waiting lines but revealing uneven distribution of workload among pumps, with some exceeding 70% utilization while others remained low. These findings highlight that while the system is generally efficient, improvements in vehicle routing and pump allocation are necessary. Recommendations include optimizing station layout, operator training, and adopting automated distribution systems to enhance efficiency and customer satisfaction.